Hosting Capacity Enhancement of Harmonically Distorted Distribution Systems Using Multi-Objective Artificial Hummingbird Algorithm - Zobaa, Ahmed M.; Shady Abdel Aleem, H. E.; Hosam Youssef, K.M. (2023 24th International Middle East Power System Conference (MEPCON), 2023)
Adding inverter-based renewables to harmonically distorted distribution systems without proper planning may lead to power quality issues, harmonic overload, overvoltage, and overheating equipment problems. Thus, the hosting capacity of the system must be controlled and enhanced so that it does not exceed the threshold value, to prevent these problems. In this paper, the enhancement of the hosting capacity of a harmonically distorted distribution system is achieved by harmonic mitigation. A damped double-tuned filter (DDTF) is utilized to reach this goal while operating the system within its acceptable operating limits according to IEEE 519 standard, the Egyptian electricity distribution code, the system voltage limitations, the transmission line thermal capacity, and the permitted power factor threshold values. A newly developed multi-objective optimization technique, namely multi-objective artificial hummingbird optimization algorithm (MOAHA), is employed to design the DDTF to maximize harmonic-constrained hosting capacity (HC HC ), minimize the system active power losses, and satisfy the pre-mentioned set of operational constraints. The results prove the superiority and effectiveness of the suggested HC HC enhancement technique.